Disentangling the circularity in sen's capability approach: An analysis of the co-evolution of functioning achievement and resources - Martin Binder; Alex Coad (Max Planck Institute of Economics, 2010)
There is an ambiguity in Amartya Sen's capability approach as to what constitutes an individual's resources, conversion factors and valuable functionings. What we here call the circularity problem points to the fact that all three concepts seem to be mutually endogenous and interrelated. All three are entangled and it can be conjectured that some functionings are resources for the achievement of other functionings, some resources can be conceived to be actually valuable functionings, and both could be conversion factors in the achievement of other functionings. To econometrically account for this interdependency we suggest a panel vector autoregression approach. We analyze the intertemporal interplay of the above factors over a time horizon of fifteen years using the BHPS data set for Great Britain, measuring individual well-being in functionings space with a set of basic functionings, comprising being happy, being healthy, being nourished, moving about freely, being well-sheltered and having satisfying social relations. We find that there are indeed functionings that are resources for many other functionings (viz. being happy) while other functionings are by and large independent, thus shedding light on a facet of the capability approach that has been neglected so far.
urn:nbn:de:gbv:27-20100623-112945-4
Keywords: I12; I31; R15; 330; capability approach; vector autoregressions; functioning selection; co-evolution of functionings; circularity problem; Capability Approach; Zufriedenheit; Schätzung; Großbritannien